Spatio-temporal distribution of the fish Synodontis schall (Teleostei: Mochokidae) in Asa lake,Ilorin, Nigeria - Araoye, P A (1999)
Spatio,temporal distribution of Synodontis scha!l in Asa lake was studied for 24 months (March 1991 to February 1993). Distribution of individual was: 28.40 % (surface), 35.60 % (shore), and 36.0 % (bottom). Catches wilhin lhe habitat were nOl significantly differen!. Similarly catches within lhe habitats during the periods of wet (May lO October) and dry (November lO April) seasons were nOl significanlly differen!. There was seasonal occurrence of lhe fish al the bottom because the catches from lhis habitat in October (4.80 to 9.10%) and November (0.00 lO 8.70%), corresponding with the period of fiood and high water levels, were relatiyely low due lO feeding and reproductive phenomena. Although catch was inversely proportional to lhe water levels, this was not significant in this experimental gil! net catches. Synodontis schall was caught throughout lhe sam, pling period indicating its successful adaptation wílhin lhe environment due to low predatíon and its díverse feeding habits